A review on bricks and stabilized compressed earth blocks - Deboucha, S.; Hashim, Roslan (2011)
This paper is a review of the state of uses of clay bricks and stabilized compressed earth blocks. We offer an overview of the world general building using clay bricks or stabilized compressed earth blocks compiled from various research organizations, modern projects which have been carried out and reports from existing manufacturing of clay bricks or stabilized compressed earth blocks. Although, stabilized compressed earth blocks as construction materials are highly unknown to most people, its advantages are seen in terms of rescuing the heritage and also as rediscovered environmentally-friendly building materials.